Experiments in evaluation capacity building: Enhancing brain disorders research impact in Ontario. (June 2020) - Nylen, Kirk; Sridharan, Sanjeev
Highlights: Support for people living with a brain disorder often takes place in the community by resource-constrained organizations. The translation and uptake of evidence in these organizations are often uneven and diffuse. ESP was created to build capacity for evaluation in partnership between community-based organizations, evaluation specialists, and funders. The Program set out to close the gap between "what works" and "what is practiced" in the community setting. Abstract: This paper is the introductory paper on a forum on evaluation capacity building for enhancing impacts of research on brain disorders. It describes challenges and opportunities of building evaluation capacity among community-based organizations in Ontario involved in enhancing brain health and supporting people living with a brain disorder. Using an example of a capacity building program called the "Evaluation Support Program", which is run by the Ontario Brain Institute, this forum discusses multiple themes including evaluation capacity building, evaluation culture and evaluation methodologies appropriate for evaluating complex community interventions. The goal of the Evaluation Support Program is to help community-based organizations build the capacity to demonstrate the value that they offer in order to improve, sustain, and spread their programs and activities. One of the features of this forum is that perspectives on the Evaluation Support Program are provided by multiple stakeholders, including the community-based organizations, evaluation team members involved in capacity building, thought leaders in the fields of evaluation capacity building and evaluation culture, and the funders.